Culture Shock Santri Luar Jawa Di Lingkungan Pondok Pesantren Di Jawa(Studi Deskriptif Kualitatif Culture Shock Santri Etnis Luar Jawa dengan Santri Etnis Jawa di Pondok Pesantren Tingkat Aliyah Al Muayyad Mangkuyudan Solo) - Pramono, Sugeng; , Agus Triyono, S.Sos, M.Si; , Rinasari Kusuma, M.I.Kom (2016)
Wander or migrate to areas that have different cultural backgrounds is a natural thing. Boarding School Al Muayyad Mangkuyudan Solo on a small ethnic origin outside Java. The purpose of this study was to determine the culture shock experienced by ethnic students outside Java and how to cope. Using qualitative research methods, while the technique of data collection by interview, observation and documentation. To analyze the collected data the author uses an interactive model. The results show the stages of culture shock experienced by ethnic students outside Java consists of four stages, namely: optimistic phase, disappointment phase, the recovery phase, and phase adjustment. Phase optimistic students assume Solo is a condensed city culture. Phase disappointment that students feel culture shock in terms of language and form of manners Java. Recovery phase is the students do the learning of the language and form of manners through close friends in the cottage. Adjustment phase of culture shock that students are able to adjust and adaptation to the language fluently and norms prevailing in the boarding school Al Muayyad Mangkuyudan Solo..